Intelligent Control of Nonlinear Systems and Nonlinear Multi-Agent Systems with Complex Constraints Unveiling Cutting-Edge Research and Insights - Ren, Hongru; Ma, Hui; Zhou, Qi; Lu, Renquan (Intelligent Control and Learning Systems, 2025)
XIII, 200 p. 75 illus., 58 illus. in color.